HUBUNGAN STATUS SOSIAL EKONOMI ORANG TUA DAN PRESTASI BELAJAR MATA PELAJARAN KEJURUAN DENGAN MINAT MELANJUTKAN KE PERGURUAN TINGGI SISWA KELAS XII PROGRAM KEAHLIAN TEKNIK KENDARAN RINGAN SMK MUHAMMADIYAH 1 BAMBANGLIPURO BANTUL TAHUN PELAJARAN2013/2014 - Herri Indra Lesmana; Tarto Sentono (Jurnal Taman Vokasi, 2014)
The purpose of the study; (1) to determine whether there is a positive relationship between socio economic standing of parents with interest to go to college; (2) to determine whether there is a positive relationship between learning achievement vocational subjects with with interest to go to college; (3) to determine whether there is a positive relationship between socio economic standing and learning achievement vocational subjects with interest to go to college.This research was conducted at Muhammadiyah 1 Vocational school of Bambanglipuro, Bantul academic year 2013/2014. The population in this study were all students of class XII Light Vehicle Enginering totaling 91 students and this study used a sampling saturated or study populations so that the entire population were sampled. This research is correlational and ex post facto categorized. Questionnaire data collection techniques and documentation of learning achivement vocational subject. The validity of the items were obtained from the product moment correlation.Â  About the reliability of the formula obtained by alpha and declared reliable. Before the data were analyzed first tested the prerequisite analysis is normality test, multicollinearity, and linearity test. Analysis using simple regression analysis and multiple regression analysis.From the analysis of the results obtained the following results: (1) There is a positive and significant relationship between socio economic standing of parents (X1) with interest to go to college (Y); (2) There is a positive and significant relationship between learning achievement vocational subjects (X2) with interest to go to college (Y); (3) There is a positive and significant relationship between socio economic standing of parents (X1) and learning achivement vocational subjects (X2) together with interest to go to college (Y).